A method for purifying the nucleocapsid protein of Nipah virus. - Tey, Beng Ti; Tan, Weng Siang; Chong, Fui Chin (2009)

(untitled)
The present invention provides a method to purify a recombinant protein from microbial cell immobilized metal affinity chromatography. The method leads to the recovery of the nucleocapsid of Nipah virus in high yields, biologically active and free from other host cell proteins.